(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2016)
We have recently build a new experimental station with a beam line dedicated to atomic collision physics at the 5 MV TANDEM accelerator of the Institute of Nuclear and Particle Physics at the National Research Center "Demokritos” in Athens, Greece. A complete zero-degree Auger projectile spectroscopy apparatus composed of a single stage hemispherical spectrograph and a 2-dimensional position sensitive detector combined with a doubly differentially pumped gas target has been set up for high resolution studies of electrons emitted from projectile ions excited in collisions with target atoms. With the new setup we have started a systematic isoelectronic investigation of K-Auger spectra emitted from pre-excited ions in collisions with gas targets using novel techniques. Here, we present some of our first new results involving collisions of carbon He-like ions with target gases. These results are expected to lead to a deeper understanding of the neglected importance of cascade feeding of metastable states in collisions of ions with gas targets and further elucidate their role in the non-statistical production of excited three-electron states by electron capture, recently a field of conflicting interpretations awaiting further resolution.